Pengaruh Terapi Kompres Jahe terhadap Tingkat Nyeri Sendi Lansia di Wilayah Puskesmas Jampang Tengah Kabupaten Sukabumi - M Altaf Hidayat; Irawan Danismaya; Amir Hamzah (Jurnal Ventilator, 2025)
High uric acid which causes joint pain is a disease where there is a buildup of purine which causes the joints to become inflamed to the point of swelling. Gout which occurs in people of course when they have a disease that causes gout they will undergo medical treatment to reduce uric acid levels and the pain that occurs in the elderly due to high levels. And most people assume that by taking medication they assume that the pain will disappear, according to Ilham (2019) that to reduce joint pain you can do ginger compress therapy on the joint pain, because the spicy effect of ginger can reduce pain in the joints. Objective: To determine the effect of ginger compress therapy on the level of joint pain in the elderly. Method: The design in this research uses a quasi-experiment using a one group pretest posttest design approach. Results: based on the results of statistical tests using the Paired Samples Test, the resulting P value is 0.000 < 0.05. Conclusion: it can be concluded that there is an influence of ginger compress therapy on the level of joint pain in the elderly in the working area of ??the Central Jampang Community Health Center. Suggestion: It is recommended for future researchers to measure the influence of respondent characteristics such as age, gender, education level, length of time suffering from joint pain, type of work and type of medication used.